The Impact of Workload and Work Stress on Turnover Intentions: The Role of Moderating Employee Well-Being - Dwinanti, Ella Karunia; Supriadi, Yudi Nur (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the impact of workload and work pressure on the intention of change with employee welfare as a moderation variable in the context of the Indonesian banking sector. Using data from 110 employees at BNI KCU Fatmawati and analyzed through the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach, the results revealed that workload (β = 0.542, p < 0.001) and work stress (β = 0.459, p < 0.001) significantly increased turnover intention. In contrast, employee well-being showed significant negative effects (β = -0.286, p < 0.001), suggesting that higher well-being reduced employee desire to leave the organization. In addition, employee well-being moderates the relationship between workload and work stress with turnover intentions, mitigating the negative effects of excessive demand. Theoretically, the study integrates the Job Demands-Resources (JD-R) and Conservation of Resources (COR) frameworks, highlighting employee well-being as a buffer mechanism that protects individuals from work-related stressors. These findings contribute a new perspective by showing that well-being is not only a result of human resource management practices but also a strategic factor that reduces withdrawal behavior. Practically, organizations must prioritize welfare-based HR policies to balance the demands of human performance and sustainability in the digital banking era.